we know that
the nth term of an arithmetic sequence can be written in the following way:
an = a1+(n - 1)d
Where a1 is the first term, and d is the common difference.
for a3=13 n=3
a3=a1+(n-1)*d----> 13=a1+(3-1)*d----> 13=a1+2*d-----> equation 1
for a17=-29 n=17
a17=a1+(n-1)*d----> -29=a1+(17-1)*d----> -29=a1+16*d-----> equation 2
using a graph tool------> to resolve the equations system
see the attached figure
the solution is
a1=19
d=-3
find a8
a1=19 d=-3 n=8
a8=19+(8-1)*(-3)----> a8=19+(-21)------> a8=-2
the answer is
a8 is -2